(untitled) (Andamios, Revista de Investigación Social, 2014)
This article presents the planning and steps carried out in the implementation of a research project financed by the Spanish Ministry of Science and Innovation (Spain). The project aimed to implement a Foreign Language teacher training model based on the development of teacher identity, using as the main instrument the trainees’ own narratives. Therefore, we conducted a longitudinal research with a group of twenty students throughout their three years of University training. Research results show evidence in the development of their reflection capacity, critical thinking, self-diagnosis and self-evaluation; and discovery of the potential of the foreign language to portray issues related to otherness and diversity.